The impact of agricultural research on productivity and poverty in sub-Saharan Africa - Alene, Arega D.; Coulibaly, O. (Elsevier, 2009)
While it is widely recognized that agricultural research is a key driver of broad-based technological change in agriculture that benefits the poor in many different ways, little is known about its aggregate impacts on productivity growth and poverty reduction in sub-Saharan Africa (SSA). Using a polynomial distributed lag structure for agricultural research within a simultaneous system of equations framework, this paper first demonstrates that agricultural research contributes significantly to productivity growth in SSA. Productivity growth is again shown to raise per capita incomes, with income increases finally having significant poverty-reducing effects. With an aggregate rate of return of 55%, the payoffs to agricultural research are also impressive. Agricultural research currently reduces the number of poor by 2.3 million or 0.8% annually. While the actual impacts are not large enough to more than offset the poverty-increasing effects of population growth and environmental degradation, the potential impacts of agricultural research are far greater. Apart from low research investments, SSA faces several constraints outside the research system that hinder realization of potential research benefits. The results show that doubling research investments in SSA would reduce poverty by 9% annually. However, this would not be realized without more efficient extension, credit, and input supply systems.